2014
DOI: 10.4103/0259-1162.134508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation fluid temperature on core temperature and hemodynamic changes in transurethral resection of prostate under spinal anesthesia

Abstract: Background:Hypothermia is a frequent observation in elderly males undergoing transurethral resection of prostate (TURP) under spinal anesthesia. The use of irrigating fluids at room temperature results in a decrease body temperature. Warmed irrigating solutions have shown to reduce heat loss and the resultant shivering. Such investigation was not much tried in low resource settings.Aim:To compare the resultant change in core temperature and hemodynamic changes among patients undergoing TURP surgery under spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Anaesthesia literature has shown that the management of core body temperatures is vital to limit iatrogenic outcomes in patients, especially in the hospital setting ( 2 , 10 ). According to these findings, advanced age, length of procedure and implementation of room temperature irrigation fluids during endoscopic procedures each increased the risk of perioperative hypothermia ( 3 , 5 , 6 ). Numerous studies also showed that decreased body temperatures increased the risk of postoperative complications ( 2 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Anaesthesia literature has shown that the management of core body temperatures is vital to limit iatrogenic outcomes in patients, especially in the hospital setting ( 2 , 10 ). According to these findings, advanced age, length of procedure and implementation of room temperature irrigation fluids during endoscopic procedures each increased the risk of perioperative hypothermia ( 3 , 5 , 6 ). Numerous studies also showed that decreased body temperatures increased the risk of postoperative complications ( 2 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many investigators have suggested that protocols such as warmed irrigation fluids should be considered when managing patients in the operating room. Few studies have evaluated this specifically in urologic patients and related procedures ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations